Utility of Expert Cue Exposure as a Mechanism to Improve Decision-Making Performance Among Novice Criminal Investigators. (June 2018) - Morrison, Ben W.; Wiggins, Mark W.; Morrison, Natalie M. V.
The research tested whether systematic exposure to expert-identified cues would improve novice criminal investigators' cue recognition and, in turn, decision making. Two studies are reported, the first of which was a pre- to postexposure assessment of 20 novices' cue recognition. This involved testing novices' recognition (accuracy and latency) of pairings of text-based labels (elicited via cognitive task analyses with subject matter experts) prior to and following an exposure phase. The results revealed statistically significant improvements in comparison with a control group. In the second study, an assessment of 36 novices' decision-making performance was undertaken prior to and following cue-based exposure (either expert or control cues). Participants engaged one of two decision tasks, which varied in the level of decision support offered: high (i.e., most pertinent features were highlighted for users) or low (i.e., features were naturally "embedded" in the task environment). Although participants receiving expert cue exposure demonstrated improvements in decision-making efficiency, advances in accuracy could be established only where a high level of support was offered. It was concluded that expert cue exposure can offer opportunities for learner development; however, a combination of exposure programs and decision support systems offers the greatest potential in improving the situation assessment skills of less experienced investigators.